Synergy of the Social Forestry Business Group (KUPS) with the Community on the Management of Pine Tree Tourism Objects in Palangka Village - Nursaifullah, Nursaifullah (LPPM Institut Studi Islam Sunan Doe, 2024)
The purpose of this study is to find out how the synergy between the social forestry business group (KUPS) and the community towards the management of the Palangka village tree tourism object. The research method used is a descriptive method with a qualitative approach. Data collection techniques are obervation, interviews, and documentation. The results from this study are that the synergy between KUPS and the community in managing pine tree tourism objects in Palangka village does not work effectively due to the lack of participation by members of the enviromental and community sreeens, even though communication and coordination have been carried out. With several application theories in management concepts which include planning, directing, evaluating it has been carried out even though it has not been fully effective due limitations in terms of capital so that it becomes one of the factors thaat hinders less developed tourist attractions.